2020
DOI: 10.1080/10428194.2020.1811860
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid receptor expression in multiple myeloma patients is a predictor of survival

Abstract: Multiple myeloma (MM) is a blood neoplasia characterized by abnormal proliferation of plasma cells. Various treatments such as stem cell transplant (SCT), proteasome inhibitors, immune-modulating drugs, monoclonal antibodies and selective inhibitors of nuclear export have been routinely used to treat MM. However, relapse and treatment resistance are common problems in MM patients. Treatments are enhanced by Dexamethasone (Dex), a synthetic steroid that activates the glucocorticoid receptor (GR) which leads to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
1
1
Order By: Relevance
“…4 O, P). For GR, this contrasts a previous study, where high expression levels at diagnosis were found predictive for OS [ 63 ]. One reason for this difference may be that Rosen and colleagues stratified patients in two subgroups, based on whether they underwent stem cell transplantation or not, and another reason may be that at that time only version IA13 of the database was available (with 650 patients vs. IA14 with 750 patients).…”
Section: Discussioncontrasting
confidence: 99%
“…4 O, P). For GR, this contrasts a previous study, where high expression levels at diagnosis were found predictive for OS [ 63 ]. One reason for this difference may be that Rosen and colleagues stratified patients in two subgroups, based on whether they underwent stem cell transplantation or not, and another reason may be that at that time only version IA13 of the database was available (with 650 patients vs. IA14 with 750 patients).…”
Section: Discussioncontrasting
confidence: 99%
“…It has reported that GR expression is a major mechanism of Dex resistance and is associated with better patient outcome in MM [3,13,15]. Consistent with previous studies, we found that GR expression showed negative correlation with Dex IC 50 values in primary MM cells (n=15) (Figure 3A).…”
Section: Sumoylation Inhibition Enhances Dex Sensitivity By Upregulating Gr Through Downregulating Mir-130bsupporting
confidence: 91%
“…Expression of SUMO E1 is upregulated in Multiple Myeloma and associated with poor prognosis mRNA pro ling of myeloma patient cohort GSE5900 showed that SUMO E1 (Ubiquitin Like Modi er Activating Enzyme 2(UBA2)/SUMO activating enzyme 2 (SAE2)) gene expression was signi cantly upregulated at the premalignant myeloma stage (MGUS) and in the asymptomatic myeloma phase (smoldering MM) compared to healthy plasma cells (supplemental Figure S1A). Moreover, higher SUMO E1 (UBA2) gene expression in MM plasma cells was associated with signi cantly shorter survival in both GSE2658 (n=559) and CoMMpass (clinical trial NCT01454297, n=764) database (Supplemental Figure S1B&C) [12,13]. These data suggest that SAE2 might be associated with therapy resistance in MM.…”
Section: Resultsmentioning
confidence: 90%